Analysis Of Merchandise Inventory Management At Distributor Cv.Muti Indofood Lestari - Azzhar, Amalina; Fathimah, Vidya (Journal of Agri Socio Economics and Business, 2023)
Study This aim For know How method management supply as well as system supply goods merchandise used by CV distributors. Muti Indofood Lestari on Jl. Tapian Nauli Pasar 3 No.47 Medan Sunggal in the recording to PT products. Two Rabbits For increase sale as well as profit company. Data analysis method used in study This that is Analysis Descriptive Comparative. Analysis used is count recording supply goods trade based on Average method (average) in effort produce profit business PT products. Dua Kelinci at CV distributor. Muti Indofood Lestari. Research results show that sale increase from January arrives by March 2023 , so there is a profit increases. CV. Muti Indofood Lestari does recording perpetually with thorough and present supervision routine so that amount supply goods always appropriate No There is error , so sale always safe and not happen loss supply lost. Recording supply goods merchandise done with good by CV. Muti Indofood Lestari.